Target orientations of the development of state policy for the sustainable development of the "green" economy in Ukraine - Bilovitska, Y. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2022)
The purpose of the article is to determine the target guidelines for the state policy of sustainable development of the "green" economy in Ukraine. The article uses general scientific and special research methods, the use of which contributed to the solution of the problem in the process of obtaining theoretical and practical results. When studying literary sources, the monographic method was used. The study of concepts, developments, approaches in order to generalize the results of scientific developments of domestic and foreign researchers to solve the problems of formation and implementation of the state policy for the sustainable development of the "green" economy, the method of systematization was used. The methods of classification, induction and deduction were used to determine the targets to which the state policy of sustainable development of the "green" economy should be directed. The abstract-logical method is used for theoretical generalizations and the formation of conclusions. It is proved that the complexity of the problem of formation and implementation of the state policy for the sustainable development of the "green" economy provides for the use of a long-term strategic approach, which will harmoniously integrate such a policy into the public administration system of Ukraine, which is in the process of reforming and adapting to European legislation, which is supported by a number of international obligations. It has been determined that the goal of state policy is to stabilize and improve the state of the environment of Ukraine in order to create an environmentally friendly natural environment for the life and health of the population, the introduction of an ecologically balanced system of nature management and the conservation of natural ecosystems, which are important for all life on planet Earth. The article proposes the Conceptual provisions for the development of a strategy for the state policy of sustainable development of the "green" economy in Ukraine, providing for a gradual move away from the traditional economy (with its areas of activity that are not energy and resource efficient and pollute the environment) to the "green" economy (which is based on qualitative structural shifts, innovative activities and industries that do not harm the environment, efficient use of natural resources, etc.).